New syllabus primary Mathematics workbook 1B - Yee Pui,Foong; Chang Suo Hui; Wong Oon Hua; Lim Li Gek Pearlyn (Karachi: Oxford university press, 2019)
"New Syllabus Primary Mathematics Workbook 1B" is an introductory educational resource designed for young learners in their first year of mathematics. It aligns with the latest curriculum standards and focuses on building a solid mathematical foundation. The book covers essential topics such as numbers, basic operations (addition and subtraction), shapes, measurements, and simple data handling. It promotes problem-solving and mathematical reasoning through engaging activities and real-life applications. With clear explanations and step-by-step examples, the book guides students in understanding key concepts while providing exercises for practice and reinforcement. Overall, it aims to foster confidence and enthusiasm for mathematics, setting the groundwork for future learning in the subject.
"New Syllabus Primary Mathematics workbook 1B" is a foundational educational resource designed for young learners in their first year of formal mathematics education. This book aligns with the latest curriculum guidelines and aims to build a strong mathematical foundation through engaging content and interactive learning experiences. The curriculum typically covers essential topics such as numbers, basic operations (addition, subtraction), shapes, measurements, and simple data handling. With a focus on developing problem-solving skills and mathematical reasoning, the book encourages students to explore concepts through hands-on activities, visual aids, and real-life applications.
Keywords: Number Sense; Mathematical Reasoning